2017
DOI: 10.1515/sbe-2017-0005
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Macroeconomic Indicators on Indian Stock Prices: An Empirical Analysis

Abstract: The purpose of the present study is to examine the long run and the short run relationship between stock price and a set of macroeconomic variables for Indian economy using annual data from 1979 to 2014. The long run relationship is examined by implementing the ARDL bounds testing approach to co-integration. VECM method is used to test the short and long run causality and variance decomposition is used to predict long run exogenous shocks of the variables. The results confirm a long run relationship among the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
46
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(67 citation statements)
references
References 45 publications
15
46
6
Order By: Relevance
“…This result indicates that GDP significantly and positively impacts on share price index, thus, Ho4 is rejected and the alternative which states otherwise accepted. This result is in harmony with the findings of (Nijam et al 2015;Giri & Joshi, 2017;Kolapo et al, 2018) while objecting the findings of Gatsimbazi et al (2018).…”
Section: Test Of Hypothesissupporting
confidence: 90%
See 3 more Smart Citations
“…This result indicates that GDP significantly and positively impacts on share price index, thus, Ho4 is rejected and the alternative which states otherwise accepted. This result is in harmony with the findings of (Nijam et al 2015;Giri & Joshi, 2017;Kolapo et al, 2018) while objecting the findings of Gatsimbazi et al (2018).…”
Section: Test Of Hypothesissupporting
confidence: 90%
“…This result implies that the inflation rate has significant negative influence on share price index and so, Ho3 is rejected and the alternative suggestion which states that inflation rate has significant influence on share price index is hereby accepted. This result is in agreement with the findings of (Talla 2013;Gatsimbazi et al, 2018) while disagreeing with the findings of (Ouma & Muriu, 2014;Giri & Joshi, 2017) whose studies revealed the inflation rate had significant positive impact on share prices. The result also conflicts with the findings of (Barno, 2014;Golam et al, 2017;Khalid & Khan, 2017) whose studies did not find inflation rate influencing share prices.…”
Section: Test Of Hypothesissupporting
confidence: 74%
See 2 more Smart Citations
“…The result of the researches said that stock price changes are influenced by macro economic factors such as the exchange rate, interest rate and Gross Domestic Product (GDP) (Mulyani, 2014). However, there are also research results which state that these three variables do not significantly influence stock prices (Chirchir, 2014), (Suriani, Kumar, Jamil, Muneer, 2015), (Giri and Joshi, 2017). Because stockis investment instruments that provide high returns, but stockis also risky, it requires knowledge about the factors that can influence stock price movements.…”
Section: Introductionmentioning
confidence: 99%